Metal‐Free Synthesis of Chlorinated β‐Amino Ketones via an Unexpected Reaction of Imines with Arylacetylenes in 1, 1, 1, 3, 3, 3‐Hexafluoro‐2‐propanol. Issue 1 (9th December 2015) - Kushwaha, Khushbu; Pinter, Balazs; Shehzadi, Syeda A.; Malakar, Chandi C.; Vande Velde, Christophe M. L.; de Proft, Frank; Abbaspour Tehrani, Kourosch
Abstract: The metal‐free reaction of terminal arylacetylenes with α, α‐dichloroaldimines in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol as the sole solvent results in the rapid and selective formation of γ, γ‐dichloro‐β‐amino ketones. In this solvent the expected dichlorinated propargylamines and/or allylic amines are not formed. The dichloromethylene moiety of the aldimine acts as an activating group and is essential to accomplish this transformation. Electron‐rich acetylenes lead to the best results and work well with all imines (with or without α′‐H at the nitrogen substituent), while electron‐deficient acetylenes only reacted with N ‐ tert ‐butylaldimines (no α′‐H). The mechanistic pathway showed 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol to protonate the aldimine, which in the rate‐determining step will react with the arylacetylene to form a resonance‐stabilized allene cation, which is trapped by a HFIP molecule giving rise to an enol ether, which promptly hydrolyzes to furnish exclusively the β‐amino ketones. Using DFT techniques we found that the first CC bond forming step is the rate‐determining step and is associated with a barrier of about 21 kcal mol −1 . Abstract :